Spatial diffusion and niche shielding dynamics: Wind power development in China - Yang, Kejia (Energy research & social science, 2023)
This paper advances the concept of niche shielding in sustainability transitions studies by refining it as a dynamic process that evolves through niche-regime interactions. It contributes to the existing literature by contesting niche shielding dynamics from two aspects: (i) how niches shield against selection pressure from multiple dimensions of the socio-technical system (science and technology, industry, market, policy, culture); and (ii) how niche shielding unfolds across multiple scales (provincial, national and global). The empirical analysis focuses on wind power development in two Chinese provinces, Inner Mongolia and Jiangsu, which serve as contrasting cases with divergent niche shielding dynamics, as well as on a national scale. The findings highlight the importance of a pluralistic and spatially sensitive understanding of niche shielding dynamics. These insights shed light on when and how to phase out strategic interventions to facilitate the diffusion of radical innovations. The coordination of niche shielding across dimensions and scales is identified as a key factor in this process. Building on these insights, the paper proposes four scenarios of niche shielding dynamics, suggesting that the trajectory of niche development can involve complex patterns that shift among these four scenarios, rather than following a linear development of step-by-step phasing out of strategic interventions. •Introduces a geographically sensitive concept of niche shielding•Provides a conceptual framework to analyse shielding dynamics across multiple dimensions and scales•Suggests a plural understanding of niche shielding dynamics•Demonstrates contrasting niche shielding dynamics in wind power development within two Chinese provinces•Presents four distinct scenarios of niche shielding dynamics